Utilisation of waste Cu-, Mn- and Fe-loaded zeolites generated after wastewater treatment as catalysts for air treatment - Stanković, Mia; Popova, Margarita; Mazaj, Matjaž; Dražić, Goran; Šuligoj, Andraž; Van de Velde, Nigel; Opresnik, Mojca; Jaćimović, Željko; Tušar, Nataša Novak; Logar, Nataša Zabukovec (Frontiers in Chemistry, 2022)
Disposal of copper, manganese and iron is especially problematic in wastewater of metallurgical and galvanization plants, the electronic industry and agriculture. On the other hand, volatile organic compounds (VOCs), emitted from industrial processes, transportation and consumer products, represent the main class of air pollutants. The study revealed the potential of waste metal-loaded zeolite, generated through wastewater treatment procedures, to be utilised as effective VOC removal catalyst for air treatment. In the first step, we have evaluated the sorption performance of natural zeolite clinoptilolite (HEU-type), and synthetic zeolite 4A (LTA-type) for a simultaneous removal of Cu2+, Mn2+ and Fe3+ species from aqueous solution. By a detailed sorption study, we determined the optimum sorption conditions and maximal metal concentrations in wastewater that can be after treatment disposed of in rivers or municipal plants. The efficiency of both zeolites for metal immobilization was demonstrated for concentrations up to 5 mg of metals / 1 g of zeolite. These waste Cu-, Mn- and Fe-loaded zeolites were thermally treated at 540 °C before the second step, where we evaluated their catalytic performance for VOC removal. The thermally treated waste Cu-, Mn- and Fe-loaded natural zeolite clinoptilolite showed good catalytic performance in total toluene oxidation as model VOC (conversion rate up to 96% at 510 °C) and cycling stability (less than 15% drop in conversion rate in 4h). In opposite, this is not the case for thermally treated waste Cu-, Mn- and Fe-loaded synthetic zeolite 4A.